KECEMASAN SOSIAL DAN PROBLEMATIC INTERNET USE PADA REMAJA - Ulfa, Fara; Winda, Yuliani (Persepsi: Jurnal Riset Mahasiswa Psikologi, 2025)
Excessive use of social media can make it harder for teenagers to manage their daily activities. This behavior is commonly referred to as problematic internet use. One factor that can contribute to an increase in problematic internet use is social anxiety. When teenagers feel anxious about interacting with their surroundings in real life, they tend to spend more time online, especially on social media, where they feel more comfortable. This study is a quantitative research aiming to examine the relationship between social anxiety and problematic internet use among teenage social media users in Pekanbaru, Indonesia. The study involved 102 teenagers aged 15-18 years as participants. The measurement tools used were the Generalized Problematic Internet Use Scale 2 (GPIUS-2) and the Anxiety Scale for Adolescents (SAS-A). The results showed that the research hypothesis was accepted, with a correlation coefficient of 0.763 and a significance value of 0.000. This means that the higher the level of social anxiety, the higher the level of problematic internet use among adolescent social media users in Pekanbaru. This study highlights the important role of parents and educators in helping teenagers manage social anxiety so that it does not lead to excessive and problematic internet use.